PEMBELAJARAN IPA BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA - Rohmani Rohmani (Universitas Muhammadiyah Kotabumi, 2019)
This paper aims to study science learning using interactive multimedia based on the level of interest in students learning. The learning interest is one of the determining factors of student learning outcomes. The students who have high learning interest in a lesson will have better outcomes than the students who have low learning interest. The ability of a teacher to help improve student learning interest is needed to improve student learning achievement. Selection of the right learning media is one of the way to help students improve their learning interest in a lesson. Interesting and interactive learning media will make students interested in using the media, so that the students' interest in learning will be indirectly more increased than before using the learning media. Interactive learning media can make students to do various movements such as eye movements in observing something that is on the learning media and also the brain movements for thinking, thus the students will be able to stay focus on the material that is being studied. The media that is capable of carrying out these functions which are then referred to as interactive multimedia.